Clinicopathological differences in attached versus loose infarcted epiploic appendages: an analysis of 52 cases. Issue 4 (1st March 2021) - Dignan, Caroline; Senior, Adya; Gonzalez, Raul S
Abstract : Background: Epiploic appendages are fatty peritoneal structures on the external surface of the colon that can infarct and become necrotic in situ or autoamputate. Aims: To describe clinicopathological features of infarcted epiploic appendages (IEAs). Methods: We reviewed 52 IEAs from 49 patients, recording numerous clinical and pathological characteristics, which were compared across attached and loose IEAs. Results: Twenty-seven IEAs were attached, and 23 were loose; location was unclear in 2. Most were incidental; 3 attached cases caused 'appendagitis'. Most (31, 60%) had a classic 'egg-like' appearance. Common findings included fat necrosis (84%), calcification (67%) and fibrosis (58%). Attached cases had a larger mean size (1.8 cm vs 1.3 cm, p=0.030) and were more often haemorrhagic (37% vs 4%, p=0.0064) and inflamed (67% vs 13%, p=0.0002). Loose cases were more often necrotic (100% vs 74%, p=0.011). Conclusions: IEAs have different morphology whether they remain attached to peritoneum or become necrotic and detached. Attached cases may cause symptoms.